2013
DOI: 10.1111/mam.12001
|View full text |Cite
|
Sign up to set email alerts
|

Bukovina blind mole rat Spalax graecus revisited: phylogenetics, morphology, taxonomy, habitat associations and conservation

Abstract: The Bukovina blind mole rat Spalax graecus is the westernmost representative of the genus and one of the least known European mammals. As currently understood, the species contains three isolates on both sides of the south‐eastern Carpathian Mountains. Our focus was on Bukovina blind mole rats from north‐eastern Romania and adjacent Ukraine, i.e. on the nominal subspecies Spalax graecus graecus Topachevskii 1976. Phylogenetic reconstruction based on 1140‐bp‐long cytochrome b sequence revealed a sister position… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
21
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 21 publications
4
21
0
1
Order By: Relevance
“…Distribution areas are based on the International Union for Conservation of Nature ( IUCN ) Red List maps, C hişamera et al . (), and our own data. A, S palax uralensis ; B, S palax giganteus ; C, S palax microphthalmus ; D, S palax arenarius ; E, S palax zemni ; F, S palax graecus s.s .…”
Section: Introductionmentioning
confidence: 51%
See 2 more Smart Citations
“…Distribution areas are based on the International Union for Conservation of Nature ( IUCN ) Red List maps, C hişamera et al . (), and our own data. A, S palax uralensis ; B, S palax giganteus ; C, S palax microphthalmus ; D, S palax arenarius ; E, S palax zemni ; F, S palax graecus s.s .…”
Section: Introductionmentioning
confidence: 51%
“…Resetnik, ; Gromov et al ., ; Pavlinov & Rossolimo, ). Nevertheless, as cytogenetic (Lyapunova, Vorontsov & Martynova, ) and molecular genetic (Hadid et al ., ) works provided further support of deep taxonomic divergences within the subfamily, and support of the presence of two genera ( Spalax and Nannospalax ), this old‐established classification scheme has finally been accepted in the most recent publications (Németh et al ., ; Arslan, Akan & Zima, , Kryštufek et al ., , Chişamera et al ., ).…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…The species composition of Spalacinae, however, has not been yet definitively settled. Chişamera et al (2014) demonstrated that the division of the extant species into two distinct genera, Spalax and Nannospalax, is justified and congruent with the pattern of phylogenetic divergence. The exceptional karyotype diversification is apparently confined to the genus Nannospalax which includes, in a traditional view, three nearly parapatric species, Nannospalax leucodon, Nannospalax xanthodon, and Nannospalax ehrenbergi (Kryštufek and Vohralík 2009).…”
Section: Introductionmentioning
confidence: 87%
“…These data enable the distribution of C-heterochromatin and nucleolar organizer regions to be revealed in the karyotype, and such findings bring new insights to the reconstruction of karyotype evolution. In this study, we follow the treatment recognizing two genera, Spalax and Nannospalax (Chişamera et al, 2014), and three traditional species within the genus Nannospalax (Kryštufek & Vohralík, 2009). …”
Section: Introductionmentioning
confidence: 99%